1999
DOI: 10.1016/s0016-7037(99)00177-5
|View full text |Cite
|
Sign up to set email alerts
|

Highly isotopically depleted isoprenoids: molecular markers for ancient methane venting

Abstract: Abstract-We propose that organic compounds found in a Miocene limestone from Marmorito (Northem Italy) are source markers for organic matter present in aneient methane vent systems (cold seeps). The limestone contains high concentrations of the tail-to-taillinked, acyclic C 20 isoprenoid 2,6,11,15-tetramethylhexadecane (crocetane), a C 25 homolog 2,6,10,15,19-pentamethylicosane (PME), and a distinctive glycerol ether lipid containing 3,7,1l,15-tetramethylhexadecyl (phytanyl-) moieties. The chemical structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
153
2
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 55 publications
13
153
2
3
Order By: Relevance
“…Hoehler et al (1994) argued on the basis of inhibition studies that the Archaea are methanogens that operate in reverse under certain conditions. In general, Elvert et al (1999) agreed with this idea, and Pancost et al (2000) and Thiel et al (1999) provided further support for the Hoehler et al (1994) proposal by showing that methane-consuming Archaea co-existed with sulfate reducers and other bacteria in cold seep sediments. In contrast, phylogenetic analyses revealed that Archaea present in California Margin sediments consist of an unidentified Methanosarcina species and apparently two new orders of Archaea (Hinrichs et al, 1999).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Hoehler et al (1994) argued on the basis of inhibition studies that the Archaea are methanogens that operate in reverse under certain conditions. In general, Elvert et al (1999) agreed with this idea, and Pancost et al (2000) and Thiel et al (1999) provided further support for the Hoehler et al (1994) proposal by showing that methane-consuming Archaea co-existed with sulfate reducers and other bacteria in cold seep sediments. In contrast, phylogenetic analyses revealed that Archaea present in California Margin sediments consist of an unidentified Methanosarcina species and apparently two new orders of Archaea (Hinrichs et al, 1999).…”
Section: Introductionsupporting
confidence: 61%
“…Similarly, hydroxyarchaeol is profoundly depleted in 13 C relative to archaeol in the lowermost mud breccia sample but has the same ␦ 13 C value in the seep. This variability is considerably greater than that previously reported, which is always less than 7‰ (Elvert et al, 1999;Hinrichs et al, 1999;Thiel et al, 1999). However, this likely reflects either the lower diversity of biomarkers or fewer sites examined in those previous studies, and we expect that this phenomenon will be widely observed in future investigations.…”
Section: Variation In Archaeal Lipid ␦ 13 C Valuesmentioning
confidence: 54%
See 1 more Smart Citation
“…Initial conditions were as follows: 37°C, pH 7, inoculum 205 ml, gas flow 20 ml min -1 (at 0°C), gas composition 5.2×10 4 Pa CO 2 , 5.2×10 4 Pa CH 4 . Polysulfides (0.5 ml, 1 M) were added as indicated tium of archaea and sulfate-reducing bacteria (Boetius et al 2000;Elvert et al 1999;Hinrichs et al 1999;Hinrichs et al 2000;Hoehler and Alperin 1996;Hoehler et al 1994;Pancost et al 2000;Thiel et al 1999;. Hoehler et al (1994) outlined a consortium hypothesis to explain anaerobic methane oxidation, in which they postulated that methanogens operate in reverse to consume methane and produce H 2 when ambient H 2 is held low by sulfate-reducing bacteria.…”
Section: Possible Hydrogen Sourcesmentioning
confidence: 99%
“…AOM is mediated by uncultured Archaea, called anaerobic methanotrophs (ANME). Specific archaeal lipids (biomarkers), from in situ samples, are highly depleted in 13 C (Elvert et al 1999(Elvert et al , 2001Hinrichs et al 1999Hinrichs et al , 2000Thiel et al 1999Thiel et al , 2001Pancost et al 2000). This is evidence that the isotopically light CH 4 (biologically produced CH 4 is depleted in 13 C) was the preferred carbon source for these microorganisms rather than other ''heavier'' carbon sources.…”
Section: Anaerobic Methanotrophsmentioning
confidence: 98%